ТО THE QUESTION OF DEVELOPING ART EDUCATION IN UKRAINE: MIRGOROD ART SCHOOL AND THE FIRST YEARS OF ITS EXISTENCE (Pedagogy of Higher and Secondary Education, 2007)
The article highlights one of the aspects of developing art education in Ukraine at the end of the 19-th and the beginning of the 20-th centuries. The detailed anafysis of researches publications in this country examines Mirgorod art school and its activities as one of the first educational establishments in the field of art, its curricula, methods  of teaching art subjects.
Keywords: art educations; at the beginning o f the 20-th century; ceramics school; methods of teaching